Investigation of the effects of Stewart platform-type industrial robot on stability of robotic milling. Issue 1 (October 2016) - Tunc, L.; Shaw, Jay
Abstract Mobile machining with industrial robots is proposed as a cost-effective and portable manufacturing alternative to large scale CNC machine tools in large-scale part manufacturing. Robotic milling, one of the widely used mobile machining approaches, involves several technical challenges and distinct characteristics in terms of machining dynamics and stability due to completely different structural build up. In this paper, distinctive effects of Stewart platform-type of hexapod robot on stability of robotic milling is investigated based on characterisation of its structural dynamics, simulation of stability limits and experimental validation. Three aspects are demonstrated: (1) the position-dependent stability diagrams due to the position-dependent dynamics of the hexapod platform, (2) the effects of cross transfer function due to the complex kinematic chain on milling stability and (3) the role of feed rate direction in stability of robotic milling. The conditions for minimised position-dependent stability through appropriate tooling are also illustrated through simulations and experimental verification. The cases where process stability may be governed by either the hexapod robot or the cutting tool modes are discussed and identified through stability analysis. It is shown that the feed rate direction becomes a significant parameter for stability limits in robotic milling. The conditions at which the cross transfer function becomes significant on milling stability are discussed through simulations and experimental results. It is shown that cross transfer functions may significantly affect milling stability especially when the radial depth of cut is less than 50 % of the tool diameter. As one of the important outcomes of this research, it is found that appropriate tooling may decrease the reliance of milling stability on robot position.